PERMAINAN TRADISIONAL KELIK-KELIKAN SEBAGAI MEDIA PENDIDIKAN KARAKTER SISWA - Putu Cory Candra Yhani; I Gd. Dedy Diana Putra (Guna Widya: Jurnal Pendidikan Hindu, 2024)
The uniqueness of culture and traditions in Bali are diverse, one of which is traditional children's games that have been played by children in Bali for generations. Of the many traditional Balinese children's games, one of them is Kelik-Kelikan. But as time goes by and the development of increasingly advanced technology, the traditional Kelik-Kelikan games are increasingly being abandoned and replaced with modern games that do not contain noble values such as the Kelik-Kelikan game. The purpose of this study was to determine the value of character education contained in tradition games in Pasraman Budi Pekerti Sri Tanjung Desa Bunutin Bangli. This research method uses a qualitative approach and phenomenological methods. Research data obtained through observation, interviews and documentation. In order to gain valid and reliable data, this research uses qualitative research methods. To produce data that is logical, this article conducts several stages of data sorting in the form of: 1). Reducing data, 2). Displaying data, 3). Verifying data and, 4). Interpreting article data. Related references greatly support the validity of a scientific work, therefore library techniques are also used through exploring literature. The results of the research found that through the application of the model, namely the democracy model, modeling model and demonstration model during the game there are Hindu religious education values that can shape student character. This research was conducted at the Budi Pekerti Pasraman Sri Tanjung, Bunutin Bangli Village, as one of the Moral-based Pasraman which still teaches traditional games as a learning medium.